Student and parent responses to online physical education learning - M. Irfan Arif; Risfandi Setyawan (Sriwijaya Journal of Sport, 2022)
The purpose of this study was to determine how students and parents respons to online learning in physical education. The data was collected by means of a questionnaire distributed online on googleform, besides that the researchers also conducted interviews with physical education teachers and the Vice Chancellor for Student Affairs to test the validity of the data. The data collected were two hundred and fourty students and two hundred and fourty parents, then analyzed by qualitative descriptive technique. The results showed that students and parents had the perception that online learning for physical education was not suitable and not effective because they had to practice directly to understand the material to the fullest. In addition, there were several obstacles, especially the availability and internet quota, students and parents admitted that they had to pay more to buy quotas. In addition, the most negative impact for students is that in the absence of practice, the mastery of movement and basic techniques in physical education material is not achieved.